2017
DOI: 10.1016/j.energy.2017.07.120
|View full text |Cite
|
Sign up to set email alerts
|

Therblig-embedded value stream mapping method for lean energy machining

Abstract: To improve energy efficiency, extensive studies have focused on the cutting parameters optimization in the machining process. Actually, non-cutting activities (NCA) occur frequently during machining and this is a promising way to save energy through optimizing NCA without changing the cutting parameters. However, it is difficult for the existing methods to accurately determine and reduce the energy wastes (EW) in NCA. To fill this gap, a novel Therblig-embedded Value Stream Mapping (TVSM) method is proposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 69 publications
0
26
0
1
Order By: Relevance
“…According to Equation (4), the coefficients in the piecewise function of spindle rotation power P rm [W] were obtained by piecewise linear regressions, and the rotation speed n m ranges from 0 to 6000 rpm with the increment of 100 rpm. The results are shown as Equation 70: According to Equation 7, all these coefficients of the function for material cutting power P cm [W] can be obtained by using Taguchi experiments and statistical regression like Lv et al [29] and Jia et al [33].…”
Section: Modeling Results Of Energy Consumption Of the Step Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Equation (4), the coefficients in the piecewise function of spindle rotation power P rm [W] were obtained by piecewise linear regressions, and the rotation speed n m ranges from 0 to 6000 rpm with the increment of 100 rpm. The results are shown as Equation 70: According to Equation 7, all these coefficients of the function for material cutting power P cm [W] can be obtained by using Taguchi experiments and statistical regression like Lv et al [29] and Jia et al [33].…”
Section: Modeling Results Of Energy Consumption Of the Step Millingmentioning
confidence: 99%
“…The value of MRR depends on the machining type and for the turning process, MRR t can be expressed as Equation 14 [33].…”
Section: Modeling Of Machining Timementioning
confidence: 99%
“…The material-drilling power is the tool-tip cutting power, and is solely related to the material removal during drilling process [20]. The material-drilling power, as an important part of total drilling power, establishing its Unfortunately, extensive studies have revealed that the energy efficiency of machine tools is generally less than 30% [11][12][13]. Therefore, the energy saving potential of machine tools is remarkable and energy efficiency improvement of machining processes has become a notable research area.…”
Section: Figurementioning
confidence: 99%
“…It can be seen that energy consumption and carbon emissions of machine tools are significant. Unfortunately, extensive studies have revealed that the energy efficiency of machine tools is generally less than 30% [11][12][13]. Therefore, the energy saving potential of machine tools is remarkable and energy efficiency improvement of machining processes has become a notable research area.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation